The implementation of the concept of individualization in training elite Female athletes with visual impairment in the sprint - Kozina, Z.; Chebanu, O.; Prokopenko, I.; Korobeynikov, G.; Korobeynikova, L.; Korobeinik, V.; Repko, O.; Kozin, S.; Osiptsov, A.; Kostiukevych, V.; Guba, A.; Trubchanikov, M.; et al. (Journal of Physical Education and Sport, 2018)
The aim of the work is to substantiate the application of the principles of individualization in the training of highly qualified athletes with visual impairment by the example of an elite athlete. Material and methods.Participants. The study involved a high-qualified athlete, specializing in short-distance running and long jump, the European Athletics Champion 2010; prize winner of the World Paralympic and Paralympic Games among athletes with visual impairments (T12 category) in 2016. Psychophysiological testing of the athlete took place in appropriate optical lenses. The course of the study. Individual characteristics of the psychophysiological state and results in running at 60 m, 80 m, 100 m, 120 m, 150 m and 200 m during five months of 2015 were analyzed. Parameters characteristic for determining the psychophysiological state, typological characteristics of the nervous system, indicators working capacity of the nervous system, attention indicators were analyzed with the help of computer programs for psychophysiological testing. Mathematical processing. Based on the results in the running on and psychophysiological indicators, a factor analysis was carried out using the main components method with Varimax rotation, multiple regression analysis by the linear model type in a step-by-step method; models of competitive performance as nonlinear sinusoidal regression using SPSS and Excel programs are compiled. Results. Four factors are identified in the individual structure of psychophysiological functions and effectiveness in running for short distances with the example of an elite sportswoman with visual impairment: 46.4% - "Fast work capacity", 8.2% - "Complicated reaction", 6.8% - "Attention ", 5.1% -" Stability ", 34% - other factors. A high contribution to the individual factor structure of psychophysiological functions and running performance of indicators reflecting the qualities characteristic of sprinters (speed of reaction and mobility of the nervous system) and nonspecific for sprinters of quality (working capacity and strength of the nervous system) is revealed. Compensatory mechanisms of visual deficiency have been identified to maintain high speed in short-distance running as psychophysiological functions: indicators characteristic of sprinters (speed of simple reaction and motility of the nervous system) and specific indicators (efficiency, strength of the nervous system). Conclusions. On the basis of mathematical models, the strengths of an athlete are highlighted, which tend to develop, and also compensate for the inadequacy of the visual analyzer.